Lymphoepithelioma-Like Carcinoma of the Breast: A Case Report Unveiling Several Clinical and Histopathological Challenges - Tarek Aridi; Mohamad Fawwaz; Ahmad Kassab; Marwan Bahmad; Faisal Houcheimi; Mohamad Mshiek; Fouad Boulos; Ali Kanj; Ghassan Ramadan; Hisham F. Bahmad; Najla Fakhruddin (Case Reports in Surgery)
Lymphoepithelioma-like carcinoma (LELC) of the breast is an extremely rare tumor type. Histologically, it mimics undifferentiated nasopharyngeal carcinoma by demonstrating nests of neoplastic epithelial cells in a background of lymphoplasmacytic infiltrates. This paper reports a 62-year-old female patient with a 3 × 1.5 cm BI-RADS type IV breast mass diagnosed on excisional biopsy as LELC. The tumor is negative for estrogen and progesterone receptors and did not overexpress HER2/neu. Routine tests for clearance before surgery were performed, and patient was managed by a modified radical mastectomy with axillary lymph node dissection showing no residual tumor. Surgical CAse REports (SCARE) guidelines were followed for reporting our case. The rarity of LELC of the breast warrants the establishment and implementation of well-defined guidelines and criteria for diagnosis and management.